An Nasawiyyah Fi Riwayat Zinah Li Nawal Al Sa’dawi - Merdu Arika (Jurnal Alsinatuna, 2017)
Literature have widely described the women existence and inequality. Feminist literary criticism is a study which focuses on analysis of women demanding justice of their existence. It also describes the elements of inequality occurred in "zeina" novel written by Nawal Al-Saadawi. The object of this research is the theory of existentialism feminism of Simone de Beauvoir who stated that women should be aware of its existence by treating themselves consciously. This research is analyzed by descriptive method. The result of this research indicates that there are some feminist elements referred to Simone de Beauvoir theory found in "zeina" novel. namely (1) personality dynamic; including willing of freedom and freedom without any regulation (2) gender consideration (3) society (4) cultural principles and (5) women’s physique. Keyword: Feminist, Existentialism, Arabic Novel